Design of a Web-Based Monitoring and Evaluation Application for Mentoring Using the Rapid Application Development Method at The Faculty of Computer Science UNIKA Santo Thomas Medan - Harianja, Andy Paul; Situmorang, Carolin Afriani (Yayasan Kita Menulis, 2024)
The academic and thesis supervision processes at the Faculty of Computer Science, UNIKA Santo Thomas Medan, currently face various challenges, including a lack of clear structure in scheduling and difficulties in monitoring student progress. To address these issues, this research aims to develop a web-based application that supports monitoring and evaluation of the supervision process. The application is designed using the Rapid Application Development (RAD) method, which facilitates flexible and responsive development tailored to user needs. With features such as supervision scheduling, student progress tracking, and automatic evaluation, this application is expected to enhance the effectiveness of supervision, facilitate communication between lecturers and students, and support more structured academic management within the faculty. The implementation of this application has successfully improved the efficiency of the supervision process and ensured that students receive more structured guidance.